The Influence of Attitude, Subjective Norms, Perceived Behavioral Control, and Financial Literacy on Investment Intention - Nurul Yulia Hidayati; Rizka Destiana (PT. Publikasiku Academic Solution, 2023)
This study aims to examine the influence of attitude, subjective norm, perceived behavioral control, and financial literacy on stock investment intention in Batam State Poyltechnic students. This study refers to the Theory of Planned Behavior (TPB) to determine the factors that influence investment intentions. The method used in this study is a quantitative method and sample selection is based on the purposive sampling. A total of 185 respondents were obtained through a questionnaires which were distributed online via Google Drive to Batam State Polytechnic students, majoring in Business Management, Managerial Accounting Study Program class of 2019-2020. Data were analyzed using Structural Equation Modelling (SEM) which is processed with SPSS 25 and AMOS 21. The result of this study show that attitude, subjective norms, and perceived behavioral control have a positive and significant effect on investment intentions. However, financial literacy does not have significant effect on investment intention.